2022
DOI: 10.1002/cam4.5263
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA HULC regulates the NF‐κB pathway and represents a promising prognostic biomarker in liver cancer

Abstract: Background Long noncoding RNAs (lncRNAs) are involved in a diverse array of biological processes. While lncRNAs are commonly upregulated in hepatocellular carcinoma (HCC), the specific regulatory roles they play in this oncogenic context require further study and clarification. Although HULC (lncRNA highly upregulated in liver cancer) is involved in disease pathogenesis, its precise role in this context remains unclear. Methods Here, we have explored the mechanistic relevance of HULC expression by assessing it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…[ 29 ] Liu et al indicated that lncRNA HULC could be served as a promising prognostic biomarker for HCC by its function in promoting HCC malignancy. [ 31 ] Another study identified the prognostic value of lncRNAs for HCC based on a small sample size of clinical samples. [ 8 , 32 , 33 ] Recent evidence has determined that BACE1-AS, [ 34 ] and LINC01093/MYLK-AS1 [ 35 ] exert prognostic value for HCC mainly by data mining based on bioinformatics tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 29 ] Liu et al indicated that lncRNA HULC could be served as a promising prognostic biomarker for HCC by its function in promoting HCC malignancy. [ 31 ] Another study identified the prognostic value of lncRNAs for HCC based on a small sample size of clinical samples. [ 8 , 32 , 33 ] Recent evidence has determined that BACE1-AS, [ 34 ] and LINC01093/MYLK-AS1 [ 35 ] exert prognostic value for HCC mainly by data mining based on bioinformatics tools.…”
Section: Discussionmentioning
confidence: 99%
“…Research methods D16366 [8] qRT-PCR, ROC, Kaplan-Meier, Cox regression analysis SNHG20 [24] qRT-PCR, Univariate and multivariate analysis, function-loss experiments DGCR5 [32] qRT-PCR, ROC, Kaplan-Meier, Cox regression analysis BANCR [25] qRT-PCR, Clinicopathologic analysis, Multivariate regression analysis, function-loss experiments AC099850 [26] TCGA datasets, function-loss experiments, geneset enrichment analysis, immune cell infiltration, immune checkpoint molecule analysis SNHG17 [27] qRT-PCR, RNA sequencing, gain-and loss-of-function studies HMMR-AS1 [28] GEO database, loss-of-function experiments in vitro and in vivo, dual luciferase report SNHG17 [30] qRT-PCR, Kaplan-Meier and log-rank analyses, Cox regression analysis, loss-of-function experiments BACE1-AS [34] TCGA mining DIO3OS [37] TCGA datasets, Kaplan-Meier, Cox regression analysis, Gene set enrichment analysis HCLNC1 [29] microarray study, In vitro cell proliferation assays and an in vivo xenotransplanted HCC tumor model CASC9 [33] RT-qPCR, Kaplan-Meier, Cox regression analysis, luciferase reporter assay LINC01093/MYLK-AS1 [35] GEO database and TCGA dataset, bioinformatic analysis, RT-qPCR INKA1-AS1 [36] TCGA and GTEx databases, Pan-cancer assay, survival analysis, immune analysis HULC [31] in vitro approaches, in vivo orthotopic HCC xenograft mouse model HCC = hepatocellular carcinoma, lncRNAs = Long noncoding RNAs.…”
Section: Lncrnamentioning
confidence: 99%